(untitled) (Eurasian Journal of Humanities and Social Sciences, 2026)
Theodore Dreiser’s “An American Tragedy” explores the unequal nature of the American Dream through the experiences of its female characters. This article examines Roberta Alden, Sondra Finchley, and the maternal figures in the novel in order to analyze how gender and class restrict women’s opportunities. The study argues that Dreiser portrays female ambition as limited by social expectations, economic dependence, and patriarchal authority. Through these characters, the novel reveals that social mobility was not equally accessible to women regardless of their social position.